Nurses' perception of preparedness for moving mental health care from psychiatric to general hospitals in Jamaica - Claudine Douglas; Aileen Standard-Goldson; Kenneth James; Wendel Abel (Pan American Health Organization, 2018)
Objectives. To examine nurses' perception of readiness to care for patients with mental illness at two general hospitals in St. Catherine, Jamaica. Methods. This mixed-methods, cross-sectional study was conducted among nurses on the medical wards of two hospitals. A 39-item, self-administered questionnaire containing open- and closed-ended questions and personal interviews was used to assess the nurses' preparedness to care for mentally ill patients; their awareness regarding protocol for care of mentally ill patients; their attitudes towards the integration of mental health care into the general hospital setting; and any associations between these and select variables, e.g., education level, work experience; and perceptions of the integration process. Results. In all, 105 nurses completed the questionnaire (response rate: 80%) and six nursing supervisors were interviewed. Almost all (99%) felt the ward was unsuitable for admitting mentally ill patients; 95% felt inadequately prepared; and 73% were not aware that a standard management protocol for treating patients with mental illness was available. Staff training was deemed important. It was felt that a special area should be established for managing mentally ill patients. Conclusions. The shift of mental health services was a strategic policy decision aligned with the recommendations and support of the Pan American Health Organization. This study shows the need for medication, equipment, implementation of standard operating procedures, adequate accommodation for patients, and staff trained to provide quality care for patients with mental illness.